Wednesday

April 23, 2014

April 23, 2014

Posted by **Ally** on Tuesday, December 18, 2012 at 7:33pm.

- Math -
**Reiny**, Tuesday, December 18, 2012 at 8:18pmt(4) = ar^3 = -4

t(8) = ar^7 = -324

divide t(8) by t(4)

r^4 = 81

r = 81^(1/4) = ± 3

if r = +3

in t(4)

a(3^3) = -4

a = -4/27

t(10) = (-4/27)(3^9) = -2916

if r = -3

a = -4/-27 = 4/27

t(10) = ar^9 = (4/27)(-3)^9 = 4(-729) = -2916

either way, t(10) = -2916

**Related Questions**

Geometric Sequence - Find the fourth term (a4) of geometric sequence if the ...

Math - A sequence is formed by adding together the corresponding terms of a ...

Geometric Sequence - The product of the first five terms of a geometric ...

Maths - 1..The first 2 terms of a geometric progression are the same as the ...

math - suppose an arithmetic sequence and a geometric sequence with common ...

math - find the fourth term of the geometric sequence whose first term is 8 and...

math - find the fourth term of the geometric sequence whose first is 200 and ...

mAtH - The 23rd term in a certain geometric sequence is 16 and the 28th term in ...

MaTh - The 23rd term in a certain geometric sequence is 16 and the 28th term in ...

MaTh - The 23rd term in a certain geometric sequence is 16 and the 28th term in ...